Masyarakat Jejaring, Media Sosial, dan Transformasi Ruang Publik: Refleksi Mengenai Fenomena Arab Spring dan “Teman Ahok” - Anggara, Satya; Pratama, Herdito Sandi (Paradigma: Jurnal Kajian Budaya, 2019)
The information technology revolution has produced a network society that Manuel Castells characterizes as space of flows and timeless time. Network logic is inclusive to various dimensions of human life and is exclusive to those who are not involved in the network. In a network society the public sphere is expanding, dynamic and increasingly interactive due to the Internet mediation. The transformation of public space also spreads political power amongst the public. An example is the birth of various volunteer groups that have extensive networks in a short time without face-to-face processes. There have also been various attempts to embrace as many groups as possible as reflected in the change of campaign strategy and regeneration by political parties. In addition, the democratization in the Arab countries (Arab Spring) was possibly happened due to the transmission of information and public consolidation which was facilitated by information and communication technology (ICT), specifically social media. The questions are, how far is the role of social media as a forum for political interaction in the network and what kind of interaction that will be formed? This article uses a qualitative approach that contains analytical description that will reflect the transformation of public space in a network society, particularly on how the democratization faces opportunities as well as challenges in its process and the role of social media in the new political interaction. Focusing on Castells’ theory of network society, this article shows that the transformation of public space at the political level has led to an existential crisis that engulfed most of political actors at this time.